Characteristics, Outcomes and Factors for Place of Death in Patients Admitted to Community-Based Palliative Care Services in Shanghai China: A Multicenter Retrospective Cohort Study - Yanxia Lin; Chuchu Yan; Dongliang Yang; Murong Zhang; Haiying Gao; Anqi Xie; Jinwen Chang; Yiwen Mao; Yongxing Shi (Palliative Medicine Reports)
Background: Community-based palliative care (CBPC) is only available in large cities in mainland China and little is known about who utilizes it. Objectives: This study examined the characteristics, outcomes, and factors associated with place of death (PoD) among inpatient CBPC patients. Design: This was a multicenter retrospective cohort study. Settings/Subjects: All patients admitted to the inpatient CBPC unit in four community health centers in 2021 in Shanghai, China, were included. Methods: Characteristics and outcome data were extracted from electronic health records and paper version notes between September 4 and December 29, 2022. PoD was followed up on May 12, 2023. Data were analyzed using descriptive analysis and categorized using two-step clustering. Decision tree analysis was used to identify factors associated with PoD. Results: The cohort admitted in 2021 included 290 participants (Age: 75.7 ± 12.7 years; Male: n = 155, 53.4%) including two children, with a mortality rate of 59.0% and a median length of stay (LoS) of 14 days upon December 29, 2022. The primary diagnosis for 80.3% of participants was tumor. Two clusters were identified. Cluster 1 was smaller than Cluster 2 (n = 45, 15.5% vs. n = 245, 84.5%) and dominated by noncancer participants (n = 37, 82.2%), whereas Cluster 2 included 91.8% (n = 225) tumor patients. Greatest significant differences in age, sex, marital status, education level, awareness of diagnosis and/or prognosis, mortality, LoS, and costs were found between the clusters. In total, 265 deaths derived from the cohort upon May 12, 2023, occur in inpatient CBPC units (75.5%), at home (18.9%), and in hospital wards (5.7%), influenced largely by participants’ marital status and age. Conclusions: Establishing contextualized inpatient CBPC services in more places nationwide that are tailored to different characteristics between cancer patients (i.e., younger and shorter inpatient stay) and noncancer patients (i.e., older and longer stay) is essential to maintain that more dying patients remain in their community.